2021
DOI: 10.1021/acsaelm.1c00855
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Band Alignments in 2D Ferroelectric α-In2Se3 Based Van der Waals Heterostructures

Abstract: Two-dimensional (2D) van der Waals (vdW) heterostructures have attracted substantial research interest in recent years, due to their tremendous advantages, such as atomically sharp interfaces, digitally controlled layered components, and unconstraint lattice mismatch, and immense potentials, in electronic and optoelectronic applications. The functionality and performance of such vdW heterostructures critically depend on the band alignment between the constituent layers. In this work, based on systematic first-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 65 publications
3
20
0
Order By: Relevance
“…As described in Section S3 of Supplementary material, we consider twelve stacking configurations of LaXY/P↓ [Figure S3] and calculate the corresponding total energy [Figure S4]. We find that the P↓ state is always energetically more stable than P↑ state, which is consistent with previously generic trend [27]. The magnetic properties can be regulated by changing the interfacial coupling, when revers the OOP polarization of In2Se3 in the LaXY/In2Se3 HS.…”
Section: Resultssupporting
confidence: 78%
“…As described in Section S3 of Supplementary material, we consider twelve stacking configurations of LaXY/P↓ [Figure S3] and calculate the corresponding total energy [Figure S4]. We find that the P↓ state is always energetically more stable than P↑ state, which is consistent with previously generic trend [27]. The magnetic properties can be regulated by changing the interfacial coupling, when revers the OOP polarization of In2Se3 in the LaXY/In2Se3 HS.…”
Section: Resultssupporting
confidence: 78%
“…Si et al reported an asymmetric metal/α-In 2 Se 3 /Si crossbar ferroelectric semiconductor junction with an ON/OFF ratio >10 4 at room temperature 36 . Also, several theoretic works have been published focusing on the band alignment of 2D α-In 2 Se 3 heterostructures controlled by the OOP polarization of α-In 2 Se 3 , which leads to about 1.1 eV potential difference between its two surfaces [37][38][39] . Ferroelectric control of the band alignment is important for the design of FTJs and other types of memory devices.…”
Section: Introductionmentioning
confidence: 99%
“…The recently discovered 2D ferroelectric materials, ,,, such as In 2 Se 3 , can be used to mediate this effect. Due to their switchable electric polarization, the 2D ferroelectrics can provide a voltage tunable interface proximity effect to other 2D materials. In particular, the electric polarization of a 2D ferroelectric is expected to efficiently control DMI in an adjacent 2D ferromagnet.…”
mentioning
confidence: 99%
“…Monolayer In 2 Se 3 contains five triangular lattices stacked with the Se–In–Se–In–Se sequence. The central Se atom is located at one of the two asymmetric but topologically identical sites, associated with a finite out-of-plane polarization pointing in opposite directions. , Recent reports show that In 2 Se 3 can be effectively used in vdW heterostructures to provide a nonvolatile control of 2D electronic structures despite very weak interlayer coupling. Due to both having hexagonal atomic structures and similar in-plane lattice constants, , Fe 3 GeTe 2 and In 2 Se 3 are well matched to construct commensurate vdW heterostructures. In such heterostructures, the and symmetries are broken, making DMI finite and thus the appearance of magnetic skyrmions possible.…”
mentioning
confidence: 99%